Lack of humoral response against Helicobacter pylori peptides homologous to human ZnT8 in Hashimoto’s thyroiditis patients - Speranza Masala; Davide Cossu; Magdalena Niegowska; Giuseppe Mameli; Daniela Paccagnini; Leonardo A Sechi (Journal of Infection in Developing Countries)
Introduction: The Helicobacter pylori (HP) reinfection rate seems to be higher in developing countries than in developed ones. An increased seroprevalence of HP has also been reported in patients with type 1 diabetes (T1D) and Hashimoto’s thyroiditis (HT). Mycobacterium avium subsp. paratuberculosis (MAP) has been linked to both T1D and HT. Quite a few lines of evidence indicate that autoantibodies against several epitopes belonging to human zinc transporter 8 (ZnT8) cross-recognize the homologous MAP3865c epitopes in both T1D and HT patients. HP may play a role in HT disease, most likely acting through a molecular mimicry mechanism that targets ZnT8 as reported for MAP and the two autoimmune diseases. Methodology: An enzyme-linked immunosorbent assay (ELISA) has been developed for the detection of antibodies against several epitopes deriving from HP proteins, which are highly homologous to the immunodominant ZnT8 peptides previously identified: ZnT8178–186 and ZnT8186–194. Results: None of the HP peptides tested were significantly recognized when the humoral responses of 92 HT patients and 91 healthy volunteers were analyzed. Conclusions: These findings do not support a triggering role for HP (through ZnT8 mimicking) in HT. If a molecular mimicry phenomenon is taking place, it involves a different self-antigen. Moreover, the negative outcome of the experiments performed stresses the fact that sharing stretches of sequence homology is relevant, but not enough to trigger an antibody-mediated cross-recognition.